2020
DOI: 10.2147/ott.s271966
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overexpression of <em>GIHCG</em> is Associated with a Poor Prognosis and Immune Infiltration in Hepatocellular Carcinoma</p>

Abstract: Purpose Hepatocellular carcinoma (HCC) is one of the most commonly diagnosed digestive cancers and the fourth leading cause of death worldwide. Long noncoding RNAs (lncRNAs) with key roles in HCC development and progression have emerged and are used in the diagnosis and prognostic prediction of HCC. The lncRNA gradually increased during hepatocarcinogenesis ( GIHCG ) is a novel lncRNA with aberrant expression in many tumors, but its prognostic value and biological role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…F11-AS1 may serve as a therapeutic target for HCC [4]. GIHCG is a biomarker that can be used to predict the prognosis of patients with HCC [10]. erefore, the study of lncRNAs as new HCC biomarkers and therapeutic targets is very important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F11-AS1 may serve as a therapeutic target for HCC [4]. GIHCG is a biomarker that can be used to predict the prognosis of patients with HCC [10]. erefore, the study of lncRNAs as new HCC biomarkers and therapeutic targets is very important.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs play a key role in the formation of cancer [8]. Growing evidence for the involvement of aberrant lncRNAs in the development and progression of HCC [4,6,9,10]. erefore, screening for lncRNAs that are clinically relevant to HCC is important for the early diagnosis and effective treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…At this time, their treatment options were already very limited, and the prognosis was often abysmal. 23 Therefore, finding meaningful biomarkers is particularly critical. SSR1 is an endoplasmic reticulum membrane receptor involved in protein translocation across the endoplasmic reticulum membrane.…”
Section: Discussionmentioning
confidence: 99%
“…That this signature was associated with immune cell infiltration and ICI treatment-related molecules (including PD-L1, PD-L2, and IDO1) suggests that it may have the potential to measure the response to ICI immunotherapy. Several studies have reported on the ability of immune-related lncRNAs to predict prognosis in HCC patients (73)(74)(75)(76). However, prospective validation in HCC patients who received ICI treatment is still lacking.…”
Section: Specific Gene Alterationsmentioning
confidence: 99%